Exploring trade union identities : union identity, Niche identity and the problem of organizing the unorganized / Bob Smale. - Smale, Bob (Bristol shorts research., 2020)
The world of work has changed and so have trade unions with mergers, rebrandings and new unions being formed. The question is, how positioned are the unions to organize the unorganized? With more than three quarters of UK workers unrepresented and the growth of precarious employment and the gig economy this topical new book by Bob Smale reports up-to-date research on union identities and what he terms 'niche unionism', while raising critical questions for the future.